2019
DOI: 10.3390/fib7100090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclic Damage on the Performance of RC Square Columns Strengthened Using Hybrid FRP Composites under Axial Compression

Abstract: The effectiveness of hybrid fibre-reinforced polymer (FRP) strengthening is evaluated for rapid repair of the pre-damaged plain concrete (PC) and reinforced concrete (RC) columns. The objective of this study is to understand the efficiency of hybrid technique for completely restoring the initial stiffness, load carrying capacity and ductility of pre-damaged columns under cyclic compression loads. Two series of PC and RC square columns were cast. The columns were pre-damaged by loading up to 80% of peak load ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 28 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…For the FE modeling of ECC members, a dynamic explicit integration procedure was used. Though the load application was made under the static scenario, a dynamic explicit procedure was used to achieve a close convergence of overall predictions [ 37 , 38 ]. The interface amid the ECC and steel was modeled using the option “embedded-region”, which does not consider the bond-slip effect.…”
Section: Resultsmentioning
confidence: 99%
“…For the FE modeling of ECC members, a dynamic explicit integration procedure was used. Though the load application was made under the static scenario, a dynamic explicit procedure was used to achieve a close convergence of overall predictions [ 37 , 38 ]. The interface amid the ECC and steel was modeled using the option “embedded-region”, which does not consider the bond-slip effect.…”
Section: Resultsmentioning
confidence: 99%
“…10. The modulus of elasticity of the longitudinal CFRP element is the same in tension and compression considering the linear material stress-strain relationship of CFRP elements [24], as per Fig. 11.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Then in terms of column repair due to cyclic loading, the results showed that the cyclic load and the resulting damage caused a reduction in the axial stiffness of all damaged specimens. Hybrid column repair can restore stiffness and strength due to axial loads (Chellapandian M, 2019).…”
Section: Introductionmentioning
confidence: 99%